2021
DOI: 10.3389/fcell.2020.609493
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Reverses the Enhanced Myocardial SR/ER–Mitochondria Interaction and Impaired Complex I-Driven Respiration in Dystrophin-Deficient Mice

Abstract: Besides skeletal muscle dysfunction, Duchenne muscular dystrophy (DMD) exhibits a progressive cardiomyopathy characterized by an impaired calcium (Ca2+) homeostasis and a mitochondrial dysfunction. Here we aimed to determine whether sarco-endoplasmic reticulum (SR/ER)–mitochondria interactions and mitochondrial function were impaired in dystrophic heart at the early stage of the pathology. For this purpose, ventricular cardiomyocytes and mitochondria were isolated from 3-month-old dystrophin-deficient mice (md… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 78 publications
5
23
1
Order By: Relevance
“…Earlier, other groups and we found significant changes in the nature of mitochondrial dysregulation in the cardiac muscle of mdx animals, which contrasted with a decrease in the functional activity of organelles in skeletal muscles already at the early stages of the development of pathology. On the contrary, in this case, we noted an increase in the functional activity of heart mitochondria accompanied by a high intensity of oxidative phosphorylation and the ability to transport and retain calcium ions in the matrix of organelles [ 15 , 16 , 17 ]. We hypothesized that such a picture might contribute to the adaptation of the heart to the development of muscular dystrophy and delay cardiac pathology.…”
Section: Introductionmentioning
confidence: 97%
“…Earlier, other groups and we found significant changes in the nature of mitochondrial dysregulation in the cardiac muscle of mdx animals, which contrasted with a decrease in the functional activity of organelles in skeletal muscles already at the early stages of the development of pathology. On the contrary, in this case, we noted an increase in the functional activity of heart mitochondria accompanied by a high intensity of oxidative phosphorylation and the ability to transport and retain calcium ions in the matrix of organelles [ 15 , 16 , 17 ]. We hypothesized that such a picture might contribute to the adaptation of the heart to the development of muscular dystrophy and delay cardiac pathology.…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, therapeutic approaches that increase mitophagy with a concomitant reduction in ROS levels have been shown to be effective in ameliorating DMD pathological outcomes. There are different ways to target this mechanism, including treating with antioxidants [ 52 , 53 ], activating the AMP kinase (AMPK) pathway [ 54 , 55 , 56 ], increasing NAD + -dependent Sirtuin 1 (SIRT1)/peroxisome proliferator-activated receptor gamma coactivator (PGC-1α) pathway [ 44 , 46 , 57 , 58 , 59 , 60 ], and upregulating mitophagy-related genes [ 39 ]. Many antioxidants have shown the therapeutic efficacy in DMD mice as seen by improvement of DMD muscle outcomes, either by acting as an ROS scavenger or by preventing the ROS formation [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, treatment with a different synthetic agonist of AMPK, metformin, in mdx mice also resulted in an amelioration of dystrophic pathology by the upregulation of PGC-1α and utrophin expression [ 74 ]. Furthermore, a recent study demonstrated that metformin treatment was also able to reduce the detrimental SR/ER-mitochondrial interaction seen in dystrophic cardiomyocytes and restore mitochondrial function [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since MAMs modulate the calcium dynamics, it has a vital role in mediating the opening of mPTP and the damage in I/R. The CypD-GRP75-IP3R-VDAC complex inhibition improved hypoxia/reoxygenation injury in cardiomyocytes [147]. The hypoxia/reoxygenation process induced the increased interaction of CypD-GRP75-IP3R-VDAC complex and GSK3β, leading to cell death.…”
Section: Regulation Of the Cardiovascular Systemmentioning
confidence: 99%